OPTIMALISASI PENGIRIMAN BARANG UNTUK MEMAKSIMALKAN GROSS PROFIT PADA PT LOGISTIK ABC - Kurniawan, Wahyu; Manalu, Haposan Vincentius; Putri, Oktaviana; Kemalaintan, Nurmasitya; Husain, Fakhril (Jurnal Ilmiah Teknik Industri, 2024)
The COVID-19 pandemic has had a significant impact on the Indonesian economy, particularly in the transportation and logistics sector. This sector has experienced fluctuations in financial performance triggered by the COVID-19 pandemic. However, after overcoming this challenging period, the Indonesian economy has shown positive trends. A leading logistics company, PT Logistik ABC, located in Jakarta, has a non-exclusive working agreement with a herbal medicine manufacturing company, PT XYZ. PT XYZ provides the required quantity of goods, but PT Logistik ABC is not obligated to fulfill the entire demand. The issue lies with PT Logistik ABC, as they transport goods from Jakarta to Semarang, but the fleet condition from Semarang to Jakarta is empty. With this situation, PT Logistik ABC aims for a higher gross profit by maximizing the available resources. Therefore, this study employs an optimization approach to optimize gross profit using non-linear programming. The optimal gross profit obtained is Rp150,893,000.00, representing 62% increase from the previous amount of Rp93,461,000.00.